Inventarisasi Jenis Jamur Makro di Kawasan Stasiun Penelitian Soraya Kecamatan Sultan Daulat Kota Subulussalam, Aceh - Angga Syatriandi; Nurhayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Macro fungi are fungi whose body parts can be seen clearly without a tool (microscope), while micro fungi are used to see their physical form using a tool (microscope). Based on the classification, mushrooms are divided into five groups, namely Chytridiomycota, Zygomycota, Glomeromycota, Ascomycota, and Basidiomycota. This study aims to determine the diversity and abundance of mushroom species found at the Soraya Research Station. The most common types were bowl and coral mushrooms, while the least common species were the bridal hood mushrooms.